PENGARUH MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2014-2019) - maryana; dasmi husin (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2021)
This study aims to examine the effect of working capital and liquidity on ROA profitability in transportation companies listed on the Indonesia Stock Exchange. The data used in this study is secondary data in the form of financial statements at PT. Adi Sarana Armada Tbk., PT. PT. Berlian Laju Tanker Tbk., PT. Cardig Aero Services Tbk., PT. Garuda Indonesia Tbk., and PT. Tanah Laut Tbk. 2014–2019 years. The data analysis method used is panel data regression analysis, namely the fixed effect model. The results show that: Partially, working capital has a statistically positive effect on profitability (ROA) of transportation companies listed on the IDX. This is indicated by a probability value of 0.48 or > 0.05. While the liquidity variable has a significant theoretical and statistical effect on profitability (ROA) of transportation companies listed on the IDX. This is indicated by a probability value of 0.35 or > 0.05. Simultaneously shows that working capital and liquidity simultaneously have a positive effect on profitability (ROA) of transportation companies listed on the IDX and also have a statistical effect. This is indicated by the value of F-count > F-table (4,47 > 2.60). Working capital and liquidity variables have the ability to explain their effect on profitability (ROA) of transportation companies listed on the IDX by 53,08%. The remaining 46,02% is influenced by other variables outside this research model.